2018
DOI: 10.1002/agm2.12045
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with medication adherence in older patients: A systematic review

Abstract: Objective Medication adherence is a major challenge in the treatment of older patients; however, they are under‐represented in research. We undertook a systematic review focused on older patients to assess the reasons underlying non‐adherence in this population. Methods We searched multiple electronic databases for studies reporting reasons for non‐adherence to medication regimens in patients aged 75 years and over. Our results were not limited to specific diseases, health‐care settings, or geographical locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 46 publications
(108 reference statements)
4
93
3
Order By: Relevance
“…This study found a weak but statistically significant correlation between the number of missed doses and the patient's age, level of education and employment status. Similar to this, reviews of non‐adherence literature have found an association with age, education and employment . In contrast, Australian studies by Laba et al and Al‐Ganmi et al found no significant correlation between non‐adherence and demographic factors .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This study found a weak but statistically significant correlation between the number of missed doses and the patient's age, level of education and employment status. Similar to this, reviews of non‐adherence literature have found an association with age, education and employment . In contrast, Australian studies by Laba et al and Al‐Ganmi et al found no significant correlation between non‐adherence and demographic factors .…”
Section: Discussionsupporting
confidence: 71%
“…Several systematic reviews have found medication non‐adherence to be associated with polypharmacy and complex regimens with higher dosing frequency . Interestingly, Smaje et al associated polypharmacy with non‐adherence but found differences across studies according to the definition of polypharmacy, namely greater than seven or nine drugs had the greatest correlation with non‐adherence while there was less association in studies using a continuous scale of pill burden .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender and age of owners were not related to medication adherence in this sample. The published literature shows that women are, in general, more adherent than men [18,19], and that having a caregiver does not necessarily improve medication adherence [20]. Although the sample had a mean age below 40 years, the lack of association between adherence and owners' age might suggest an opportunity to use m-health apps independently from the age of the caregiver.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, polypharmacy has been found to be associated with a variety of negative outcomes in older adults, such as falls, mental impairment, cognitive decline, increase of hospital length-of-stay and readmission [11][12][13]. Another important problem is the lack of therapy adherence, given that complex therapeutic regimes are di cult to manage properly [14,15].…”
Section: Introductionmentioning
confidence: 99%